Peran orangtua dalam pendidikan seksual anak: Membangun kesehatan reproduksi - Murti, Mitra Dwi (Maliki Interdisciplinary Journal, 2024)
Sexual education is an important component in building children's reproductive health. Parents as the main figures in children's lives have a crucial role in providing appropriate and age-appropriate sexual education. Parents need to create an atmosphere of open and supportive communication so that children feel comfortable asking and discussing sexuality. Parents must provide children with information that is accurate and appropriate to their developmental age. This information includes education about body anatomy, reproduction, puberty, sexual relations, and preventing sexual risks. Parents need to instill moral and ethical values ​​related to sexuality, such as love, affection, mutual respect and responsibility. Parents must demonstrate behavior that is in accordance with the values ​​taught to their children. This is important to build parents' trust and credibility as a source of information and role models for children.